Adolescent rape: Characteristics and short-term impact - Titis Prawitasari; Hartono Gunardi; Bambang Madiyono; Rosdiana S Tarigan (Paediatrica Indonesiana, 2005)
Background Data in Indonesia show that adolescents still havethe highest rate for rape and other sexual assaults among agegroup. There are gender differences in adolescent rape and sexualassault, with female victims exceeding males with a ratio of 3:1.Sexual assault and rape can affect numerous children and oftenlead to short-term and long-term consequences.Objectives To determine the characteristics and short-term im-pacts of adolescent rape.Methods A cross-sectional study was conducted on 31 adoles-cents who had been raped 1-9 months previously. Subjects andparents were assessed using Child Behavior Checklist, Draw aPerson, House Tree Person, and Raven’s Progressive Matrices todetermine psychological problems. History and physical examina-tion findings at the time of rape were reviewed.Results Thirty out of 31 female adolescents were 13-18 years old.Almost half of them came from low income families and large fam-ilies, two-thirds of all subjects were living with their parents. Nine-teen of 31 perpetrators were friends or acquaintances, only 4 wererelatives. Tears of hymen were found in 21 subjects and only 8 ofthem had non-genital injuries. Nine of 31 subjects had a high aver-age range in non-verbal processing. Most subjects had a greattendency to feel insecure, anxiety, depression, and had interper-sonal relationship problems. Regression and aggressiveness werefound in almost half of the subjects. All subjects felt that theirmothers were protective and half of them had dominant fathers.Conclusion Almost half of the adolescent victims come from low-economic status and large families, most of the assailants werefriends or acquaintances. Adolescent rape victims have ongoingbehaviour problems. The most common problems are anxiety,depression, and relationship problems